2016
DOI: 10.1523/jneurosci.4527-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

ADrosophilaModel of Neuronopathic Gaucher Disease Demonstrates Lysosomal-Autophagic Defects and Altered mTOR Signalling and Is Functionally Rescued by Rapamycin

Abstract: Glucocerebrosidase (GBA1) mutations are associated with Gaucher disease (GD), an autosomal recessive disorder caused by functional deficiency of glucocerebrosidase (GBA), a lysosomal enzyme that hydrolyzes glucosylceramide to ceramide and glucose. Neuronopathic forms of GD can be associated with rapid neurological decline (Type II) or manifest as a chronic form (Type III) with a wide spectrum of neurological signs. Furthermore, there is now a well-established link between GBA1 mutations and Parkinson's disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
130
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 53 publications
(43 reference statements)
18
130
1
Order By: Relevance
“…Unexpectedly we found that p-MTOR and p-RPS6 protein levels were decreased in Gba L444P/WT mouse brains. While contrary to our observation of suppressed autophagy induction, these data are consistent with recent studies in GD and GBA-PD patient-derived fibroblasts [49] and Gba1 -deficient Drosophila models [50] in which the hypoactive MTOR was proposed to be responsible for impaired recycling of functional lysosomes from autolysosomes.…”
Section: Discussionsupporting
confidence: 90%
“…Unexpectedly we found that p-MTOR and p-RPS6 protein levels were decreased in Gba L444P/WT mouse brains. While contrary to our observation of suppressed autophagy induction, these data are consistent with recent studies in GD and GBA-PD patient-derived fibroblasts [49] and Gba1 -deficient Drosophila models [50] in which the hypoactive MTOR was proposed to be responsible for impaired recycling of functional lysosomes from autolysosomes.…”
Section: Discussionsupporting
confidence: 90%
“…In the initial characterization of our Drosophila GBA-deficient model we found accelerated insoluble ubiquitinated protein aggregates, accumulation of Ref(2)P, and oligomerization of ectopically expressed human a-synuclein in Gba1b mutants, suggesting an impairment in lysosomal degradation [18,42]. A similar GBA-deficient Drosophila model also found evidence of lysosomal dysfunction, including enlarged lysosomes in GBA-deficient brains [43]. However, our proteomic analysis of Gba1b mutants did not support a profound impairment in autophagy, but instead suggested dysregulation of EVs with altered protein cargo which could be suppressed locally with knockdown of genes encoding ESCRT machinery important for EV biogenesis [19].…”
Section: Discussionmentioning
confidence: 67%
“…The pathophysiological mechanisms of neurological involvement remain poorly explained; GlcCer turnover in neurons is low and its accumulation is only significant when residual GCase activity is drastically decreased, i.e., only with some types of GBA1 mutations [9]. Consistent with this, recent work on a Drosophila model of neuronopathic GD demonstrated autophagy impairment in the GCase-deficient fly brains [10]. Very rarely, GD may be caused by a mutation in the PSAP gene, leading to a deficiency in saposin C without GCase deficiency [3].…”
Section: Pathophysiologymentioning
confidence: 94%